Experimental investigation on melting and solidification behaviour of erythritol in a vertical double spiral coil thermal energy storage system. (January 2019) - Anish, R.; Mariappan, V.; Suresh, S.
Highlights: A novel double spiral coil ESU is developed for analysing the energy storage and discharge characteristics of medium temperature PCM (Erythritol). Energy storage rate, energy discharge rate and the influence of changing the inlet temperature and flow rate of the HTF were analysed. The double spiral coil tube significantly enhanced the heat transfer performance of the ESU. Natural convection plays a dominant role during charging (melting), and conduction dominates during discharging (solidification). The results of the present study will be beneficial for the design of solar PCM based domestic water heating units and vapour absorption refrigeration system. Abstract: An experimental setup for a double spiral coil phase change material (PCM) energy storage unit (ESU) is designed and fabricated to study the melting and solidification characteristics of erythritol. The analysis includes the study of melting and solidification behaviour, energy storage rate, energy discharge rate and the influence of changing the inlet temperature and flow rate of the heat transfer fluid (HTF) therminol-55. The melting process carried out by supplying high-temperature HTF at different temperature of 145, 150, and 155 °C and soldification process carried out by supplying low-temperature HTF at different temperature of 40, 45 and 50 °C. The HTF flow rate for both melting and soldification process was maintained at 1.5, 2 and 2.5 litres per minute (lpm). The double spiral coil tube significantly enhanced the heat transfer performance of the ESU. The time required for melting the PCM increases as the flow rate and the inlet temperature of the HTF decreases. Conduction generally controls PCM solidification, and the temperature variations of PCM in the storage unit were almost same with negligible variations during the solidification process. As compared to the melting process the HTF flow rate does not have a significant influence on the solidification process.